If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -2(g + 4) = 8(g + -1) Reorder the terms: 3g + -2(4 + g) = 8(g + -1) 3g + (4 * -2 + g * -2) = 8(g + -1) 3g + (-8 + -2g) = 8(g + -1) Reorder the terms: -8 + 3g + -2g = 8(g + -1) Combine like terms: 3g + -2g = 1g -8 + 1g = 8(g + -1) Reorder the terms: -8 + 1g = 8(-1 + g) -8 + 1g = (-1 * 8 + g * 8) -8 + 1g = (-8 + 8g) Add '8' to each side of the equation. -8 + 8 + 1g = -8 + 8 + 8g Combine like terms: -8 + 8 = 0 0 + 1g = -8 + 8 + 8g 1g = -8 + 8 + 8g Combine like terms: -8 + 8 = 0 1g = 0 + 8g 1g = 8g Solving 1g = 8g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-8g' to each side of the equation. 1g + -8g = 8g + -8g Combine like terms: 1g + -8g = -7g -7g = 8g + -8g Combine like terms: 8g + -8g = 0 -7g = 0 Divide each side by '-7'. g = 0 Simplifying g = 0
| 4+-(t+-24)+38t-38=0 | | 28+-6+x=40 | | 2/5=3/y-3 | | 18+-13+n=9 | | 8=1/2(3x-8) | | 3(4z-8)=6z-8 | | 25x-12=33 | | x/5-5=x/7- | | 45+36u=97+23u | | 12÷3/8= | | 8x+4(7-2x)= | | x-7=18+x | | x+1.3=0.6x | | -4(v-2)=-4(v-8)-v | | x+1.3=0.6 | | 12/30-2/5 | | -3(5x-3)=-6 | | 2x-6-(5x+1)=4-2x-(3x-1) | | x^2=14x+13 | | 8050=0.115x | | 5x-y=34 | | 4(3x-8)-10x-8=10 | | 167-8*4-23= | | 18x^4+69x^3-105x^2=0 | | 9-2a=53 | | 2n/3-1/4=7/4 | | 4/5u-3=-5/3u-7/3 | | 3(x-4)+5x=-3(x+4)+11x | | 9m=-11+8m | | 2(4x+4)=56 | | N/-39=-101 | | 18x-84=(-6) |